Acoustic and non-acoustic performance of coal bottom ash as sound absorptive material for reducing railway noise level - Ramzi Hannan, Nurul Izzati Raihan (2019)
The development of new technology and rapid development in many countries have led to various types of pollution, especially acoustic pollution in urban areas. Furthermore, the huge production of Coal Bottom Ash (CBA) is treated as waste and often placed into impoundment ponds, silos or landfills, which has contributed to environmental issues. Usage of CBA in concrete production in reducing railway noise pollution reduce the environmental pollution. This study presents the acoustic and non-acoustic performance for a new concrete product that consists mainly of CBA. Grade 30 MPa concrete was cast with varying replacement percentages (0% to 100%) of CBA as fine aggregate replacement in concrete mixture. The specimens were cured for periods of 7, 28 and 90 days. The non-acoustic performance of CBA concrete demonstrated similar or even better performance than normal concrete by conducting compressive strength, splitting tensile strength, water absorption, water permeability and ultrasonic pulse velocity. The increase in CBA percentage in the concrete mixture has affected the compressive strength and splitting tensile strength of the sample which were lower than that of control concrete. CBA concrete can be recommended as good concrete due to its absorption properties. Based on the sound test conducted according to ISO 11654: 1997, it was found that CBA concrete can be classified as Class D (absorption). Class D materials are able to absorb more than 30% of sound by conducting impedance tube and reverberation time. In addition, the Noise Reduction Coefficient (NRC) performance for CBA concrete addresses more than 35% of the absorbed railway sound. CBA concrete showed an improvement in acoustic properties compared to normal concrete as it is able to reduce up to 3.74 dB of the existing railway noise level while normal concrete can only reduce up to 1.94 dB of the existing noise level.